Alum: an efficient catalyst for one-pot synthesis of alpha-aminophosphonates - Sonar, Swapnil S.; Shelke, Kiran F.; Kakade, Gopal K.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Chinese Chemical Letters, 2009)
Alum (KAl(SO(4))(2)center dot 12H(2)O) is an inexpensive, efficient, non-toxic and mild catalyst for the one-pot synthesis of alpha-aminophosphonates. A three component reaction of an aldehyde/ketone, an an-tine and triethyl phosphite was carried out under solvent-free conditions to afford the corresponding alpha-aminophosphonates in short reaction times and high yields with the green aspects by avoiding toxic catalysts and solvents. (C) 2009 Murlidhar S. Shingare. Published by Elsevier B.V. on behalf of Chinese Chemical Society. All rights reserved.
Keywords: Aldehyde/ketone; alpha-Aminophosphonates; Alum; Amine; Solvent-free; Triethyl phosphite

Alum catalyzed convenient synthesis of quino [2,3-b][1,5]benzoxazepine alpha-aminophosphonate derivatives - Sonar, Swapnil S.; Sadaphal, Sandip A.; Shitole, Nana N.; Jogdand, Nivrutti R.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Bulletin of the Korean Chemical Society, 2009)
We have described an efficient synthesis of quino[2,3-b][1,5]benzoxazepine alpha-aminophosphonate derivatives by the nucleophilic addition of triethyl phosphite to substituted quino[2,3-b][1,5]benzoxazepines promoted by easily available, inexpensive and mild catalyst KAl(SO(4))(2)center dot 12H(2)O (alum). The reactions proceed smoothly at room temperature under solvent-free reaction conditions and providing high yield of product in very short reaction time.
Keywords: 5]benzoxazepine; alpha-Aminophosphonate; Alum; Quino[2.3-b][1; Solvent-free; Triethyl phosphite

Ammonium metavanadate: an effective catalyst for synthesis of alpha-hydroxyphosphonates - Sonar, Swapnil S.; Kategaonkar, Amol H.; Ware, Madhav N.; Gill, Charansingh H.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Arkivoc, 2009)
Ammonium metavanadate (NH(4)VO(3)) is an inexpensive, efficient and mild catalyst for the synthesis of alpha-hydroxyphosphonate derivatives by the reaction of various aryl or heteroaryl aldehydes with triethylphosphite at room temperature. This method affords the alpha-hydroxyphosphonates in short reaction times, under solvent-free conditions, and in high yield.
Keywords: Aldehyde; alpha-hydroxyphosphonate; Ammonium metavanadate (NH(4)VO(3)); Solvent-free; Triethyl phosphite